Expanded particles

Foamed particles with a mixed resin of polyamide and polyarylene sulfide address the issues of shrinkage and appearance in polyamide resin foam moldings by enhancing moldability and fusion properties, resulting in high-quality molded products.

JP7602420B2Active Publication Date: 2024-12-18JSP CORP
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2021062220
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2024-12-18
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Polyamide resin foam moldings face challenges with high shrinkage rates, poor fusion and recovery properties, and unsatisfactory appearance due to their crystallinity and limited moldability, making it difficult to produce high-quality foamed molded products.

Method used

The development of foamed particles with a specific apparent density and a mixed resin composition of polyamide resin and polyarylene sulfide resin, with a controlled ratio and properties such as cell diameter and heat stabilizers, to enhance moldability and reduce shrinkage.

Benefits of technology

The solution results in foamed particles that suppress molding shrinkage, exhibit excellent fusion and recovery properties, and produce molded articles with a good appearance, maintaining dimensional accuracy and improved physical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007602420000003
    Figure 0007602420000003
  • Figure 0007602420000001
    Figure 0007602420000001
  • Figure 0007602420000002
    Figure 0007602420000002
Patent Text Reader

Abstract

To provide expanded beads which suppress molding shrinkage after molding, are excellent in fusion property and recoverability, and have good appearance.SOLUTION: Expanded beads contain a mixed resin of a polyamide-based resin and a polyarylene sulfide-based resin as a base material resin, wherein apparent density of the expanded beads is 10-300 kg / m3, and a blended ratio of the polyarylene sulfide-based resin to 100 pts.mass of the polyamide-based resin is 5-40 pts.mass.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to expanded beads, and more particularly to expanded beads having a mixed resin of a polyamide resin and a polyarylene sulfide resin as a base resin. [Background technology]

[0002] Polyamide resins are known as plastics with high heat resistance and excellent abrasion resistance, chemical resistance, etc. Foamed molded articles obtained by foaming these polyamide resins can be made lighter while retaining excellent properties such as heat resistance, abrasion resistance, and chemical resistance, and are therefore expected to be used in a wider range of applications such as automobile parts and electrical products. Although polyamide resin foamed molded products have the above-mentioned excellent properties, they have poorer foaming properties than general-purpose resins due to their crystallinity, and it is difficult to obtain molded products with high foaming ratios due to limited molding conditions. Therefore, attempts have been made to use additives to improve moldability. For example, Patent Document 1 discloses a foamable polyamide resin obtained by adding a trifunctional compound, an unsaturated carboxylic acid anhydride, a copolymer of styrene, an olefin, or the like, or a polycarbonate resin as a modifier to a polyamide resin, melt-kneading the resulting composition, and foaming the composition, with the aim of obtaining a foamed board that is uniformly and finely foamed and has a small open cell ratio. Furthermore, Patent Document 2 discloses a polymer foam obtained from a thermoplastic molding material containing a crosslinked copolymer containing a thermoplastic polyamide and a component such as itaconic acid. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2000-103960 A [Patent Document 2] Special Publication No. 2011-526315 Summary of the Invention [Problem to be solved by the invention]

[0004] By using expanded polyamide resin particles as a raw material for foamed molded articles, foamed molded articles of various shapes can be obtained by adjusting the particle distribution to suit the mold. As described above, polyamide resin foamed molded articles have excellent light weight, but have a problem of a large shrinkage rate after molding. In addition, due to the difficulty of molding, there is a risk of poor fusion property and recovery property, and the appearance of the obtained foamed molded article is poor in gloss and voids are likely to be observed. Therefore, there has been a demand for a polyamide resin foamed bead molded article that is excellent in fusion property and recovery property during production, has little molding shrinkage after molding, and has a good appearance. Therefore, the problem to be solved by the present invention is to provide expanded beads which can be used to produce expanded bead moldings that are suppressed from undergoing molding shrinkage after molding, have excellent fusibility and recovery properties, and have a good appearance. [Means for solving the problem]

[0005] As a result of intensive research into the above-mentioned problems, the inventors have found that expanded beads having an apparent density within a specific range and a base resin that is a mixed resin of a polyamide-based resin and a polyarylene sulfide-based resin in a specific ratio can solve the above-mentioned problems.

[0006] That is, the present invention provides the following [1] to [8]. [1] Expanded beads having a mixed resin of a polyamide resin and a polyarylene sulfide resin as a base resin, the expanded beads having an apparent density of 10 to 300 kg / m 3 The expanded beads have a compounding ratio of the polyarylene sulfide resin of 5 to 40 parts by mass per 100 parts by mass of the polyamide resin. [2] The expanded particles according to [1] above, wherein the polyarylene sulfide resin is a polyphenylene sulfide resin. [3] The expanded beads according to the above [1] or [2], wherein the expanded beads have an average cell diameter of 30 to 150 μm. [4] The expanded beads according to any one of the above [1] to [3], wherein the polyamide resin is a polyamide copolymer having a melting point of 185 to 250°C. [5] The expanded beads according to any one of the above [1] to [4], wherein the difference [Tm2-Tm1] between the melting point (Tm1) of the polyamide resin and the melting point (Tm2) of the polyarylene sulfide resin is 70 to 130°C. [6] The expanded beads according to any one of the above [1] to [5], comprising one or more heat stabilizers selected from the group consisting of hindered amine compounds, hindered phenol compounds, and phosphorus compounds. [7] The expanded beads according to any one of the above [1] to [6], wherein the expanded beads contain carbon black. [8] An expanded bead molding in which the expanded beads according to any one of the above [1] to [7] are fused to each other. Effect of the Invention

[0007] According to the present invention, there can be provided expanded beads which can be used to produce expanded bead moldings that are suppressed from undergoing molding shrinkage after molding, have excellent fusibility and recovery properties, and have a good appearance. [Brief description of the drawings]

[0008] [Figure 1] 1 is an example of a DSC curve obtained by heat flux differential scanning calorimetry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] [Foam particles] The expanded beads of the present invention are expanded beads having a mixed resin of a polyamide resin and a polyarylene sulfide resin as a base resin, and have an apparent density of 10 to 300 kg / m 3 The blending ratio of the polyarylene sulfide resin to 100 parts by mass of the polyamide resin is 5 to 40 parts by mass.

[0010] (Polyamide resin) Examples of the polyamide-based resin constituting the mixed resin that is the base resin of the expanded beads of the present invention include polyamide and polyamide copolymers, and polyamide copolymers are preferred. Polyamides include, for example, poly(6-aminohexanoic acid), also known as poly(caprolactam) (polycaproamide, nylon 6), poly(laurolactam) (nylon 12), poly(hexamethylene adipamide) (nylon 66), poly(7-aminoheptanoic acid) (nylon 7), poly(8-aminooctanoic acid) (nylon 8), poly(9-aminononanoic acid) (nylon 9), poly(10-aminodecanoic acid) (nylon 10), poly(11-aminounsodium EDTA) (nylon 11), poly(12-aminobutanoic acid) (nylon 12), poly(1 ... Examples of the homopolymers include poly(hexamethylene sebacamide) (nylon 11), poly(hexamethylene sebacamide) (nylon 610), poly(decamethylene sebacamide) (nylon 1010), poly(hexamethylene azelamide) (nylon 69), poly(tetramethylene adipamide) (nylon 46), poly(tetramethylene sebacamide) (nylon 410), poly(pentamethylene adipamide) (nylon 56), and poly(pentamethylene sebacamide) (nylon 510). The polyamide copolymer means a homopolymer having two or more kinds of repeating units, and at least a part of each repeating unit has an amide bond. Examples of polyamide copolymers include polycaproamide / polyhexamethylene adipamide copolymer (nylon 6 / 66), caprolactam / hexamethylenediaminoadipic acid / lauryl lactam (nylon 6 / 66 / 12), and caprolactam / lauryl lactam copolymer (nylon 6 / 12). The polyamide resin may be a single polyamide or a polyamide copolymer, or a combination of two or more polyamides. Among the above polyamide resins, a polyamide resin that is a combination of one or two or more selected from nylon 6, nylon 66, nylon 6 / 66, and nylon 6 / 66 / 12 is preferred, and a combination of one or two selected from nylon 6 / 66 and nylon 6 / 66 / 12 is more preferred.

[0011] The polyamide copolymer may be a block copolymer in which a certain amount of amides of the same repeating unit are followed by a certain amount of amides of different types, or a random copolymer in which different types of amides are randomly repeated, but is preferably a random copolymer. If the polyamide copolymer is a random copolymer, it becomes possible to mold the expanded beads at a relatively low molding pressure when molding them in a mold.

[0012] The polyamide resin used in the present invention preferably has a flexural modulus of 1000 MPa or more, more preferably 1200 MPa or more, and even more preferably 1500 MPa or more. The amide elastomer generally has a flexural modulus of 600 MPa or less. If the flexural modulus of the polyamide resin is within the above range, it is preferable because the high flexural modulus makes it difficult to shrink even when exposed to room temperature after foaming, and it is easy to obtain expanded beads with a high expansion ratio. In addition, the high flexural modulus makes it preferable because it has excellent moldability in a mold. The upper limit of the flexural modulus of the polyamide resin is approximately 3000 MPa.

[0013] The flexural modulus of polyamide-based resins can be determined by measuring a test piece in accordance with JIS K7171:2016 after leaving the test piece at rest for 24 hours at a temperature of 23°C and a humidity of 50%.

[0014] The polyamide resin used in the present invention has a density of 1.05 g / cm 3 It is preferable that the content is 1.1 g / cm or more. 3 The density of the amide elastomer is preferably about 1.05 g / cm or more. 3 The density can be determined according to the method described in ISO 1183-3.

[0015] The polyamide resin used in the present invention is preferably a terminal-blocked polyamide resin in which the functional groups at the molecular chain ends are blocked, which can more reliably suppress hydrolysis during the production process of the expanded beads, and makes it easier to obtain expanded beads that can withstand molding in a mold. Furthermore, the durability of the expanded bead molding (hereinafter, simply referred to as "molded article") obtained by molding in a mold is improved. As the terminal blocking agent for blocking the molecular chain terminals, for example, a carbodiimide compound, an oxazoline compound, an isocyanate compound, an epoxy compound, etc. can be used. Among these, carbodiimide compounds are preferred. Specific examples include aromatic monocarbodiimides such as bis(dipropylphenyl)carbodiimide (e.g., "Stabaxol 1-LF" manufactured by Rhein Chemie), aromatic polycarbodiimides (e.g., "Stabaxol P", "Stabaxol P100", "Stabaxol P400" manufactured by Rhein Chemie), and aliphatic polycarbodiimides such as poly(4,4'-dicyclohexylmethanecarbodiimide) (e.g., "Carbodilite LA-1" manufactured by Nisshinbo Chemical Co., Ltd.). These end-capping agents may be used alone or in combination of two or more. The amount of the end blocking agent is preferably 0.1 to 5 parts by mass, and more preferably 0.5 to 3 parts by mass, based on 100 parts by mass of the polyamide resin. As described above, the polyamide-based resin used in the present invention is preferably a polyamide-based resin end-blocked with one or more end-blocking agents selected from a carbodiimide compound, an epoxy compound, an isocyanate compound, and the like, and more preferably a polyamide-based resin end-blocked with a carbodiimide compound.

[0016] (Polyarylene sulfide resin) Polyarylene sulfide resins are polymers whose main repeating unit is -(Ar-S)- (wherein Ar is an arylene group). Examples of the arylene group in the polyarylene sulfide resin constituting the mixed resin that is the base resin of the expanded beads of the present invention include p-phenylene group, m-phenylene group, o-phenylene group, substituted phenylene group, p,p'-diphenylene sulfone group, p,p'-biphenylene group, p,p'-diphenylene ether group, p,p'-diphenylene carbonyl group, naphthalene group, etc. Among these, the p-phenylene group is preferred. The polyarylene sulfide resin constituting the mixed resin that serves as the base resin of the expanded beads of the present invention is preferably a polyphenylene sulfide resin. The polyarylene sulfide resin may be any of a crosslinked type, a semi-crosslinked type, and a straight-chain type, but the straight-chain type is preferred from the viewpoint of excellent flowability when the resin is melt-kneaded in an extruder.

[0017] The base resin of the expanded beads in the present invention is a mixed resin of a polyamide resin and a polyarylene sulfide resin. In the expanded beads of the present invention, the blending ratio of the polyarylene sulfide resin to 100 parts by mass of the polyamide resin is 5 to 40 parts by mass. The blending ratio of the polyarylene sulfide resin to 100 parts by mass of the polyamide resin is preferably 10 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 20 parts by mass or more. The blending ratio of the polyarylene sulfide resin to 100 parts by mass of the polyamide resin is preferably 30 parts by mass or less, more preferably 25 parts by mass or less, and even more preferably 20 parts by mass or less. It is known that when a thermoplastic resin is molded in a mold, the molded body obtained shrinks to become smaller than the internal dimensions of the mold. In particular, in the case of polyamide resins or foams, the molded body obtained tends to have large mold shrinkage. By having the blending ratio of the polyarylene sulfide resin within the above range, mold shrinkage after molding the expanded beads in a mold can be significantly suppressed while maintaining moldability. By suppressing the mold shrinkage rate of the molded body to a low level, a molded body close to the internal dimensions of the mold can be obtained, so that a molded body with high dimensional accuracy can be obtained. In addition, a curing process is usually performed after molding for the expanded bead molded body, but in the case of a molded body with a small mold shrinkage rate, the time of the curing process can be shortened.

[0018] In the present invention, the reason why the molding shrinkage rate after molding the expanded beads in a mold can be suppressed to a low level is considered to be as follows. When molding the expanded beads in a mold, many of the crystalline components of the polyamide resin are melted by heating and pressurizing with steam, but since the melting point of the polyarylene sulfide resin is higher than that of the polyamide resin, it is considered that the crystalline components of the polyarylene sulfide resin are difficult to melt. After molding in a mold, the resin crystallizes as the temperature and pressure decrease. At this time, the crystalline components of the polyarylene sulfide resin that remain unmelted suppress the volumetric shrinkage at this time, so that the molding shrinkage rate is suppressed to a low level.

[0019] (Heat stabilizer) The heat stabilizer in the present invention has the effect of suppressing deterioration of the resin due to heat when the expanded beads or the expanded bead molding is placed in a high temperature environment. The expanded beads of the present invention preferably contain a heat stabilizer. More preferably, the expanded beads of the present invention contain one or more heat stabilizers selected from the group consisting of hindered amine compounds, hindered phenol compounds, and phosphorus compounds from the viewpoint of further improving weather resistance. The expanded beads of the present invention more preferably contain one or more heat stabilizers selected from the group consisting of hindered amine compounds, hindered phenol compounds, and phosphorus compounds, further preferably contain two or more heat stabilizers selected from the group consisting of hindered amine compounds, hindered phenol compounds, and phosphorus compounds, and further preferably contain three or more heat stabilizers selected from the group consisting of hindered amine compounds, hindered phenol compounds, and phosphorus compounds. In the case where a plurality of heat stabilizers are contained, preferably, one or more heat stabilizers are selected from hindered amine compounds and one or more heat stabilizers are selected from hindered phenol compounds, and more preferably, one or more heat stabilizers are selected from hindered amine compounds, one or more hindered phenol compounds, and one or more heat stabilizers are selected from phosphorus compounds.

[0020] A specific example of the hindered amine compound is Bis(2,2,6,6,-tetramethyl-4-piperidyl)sebacate (trade name: Tinuvin770, manufactured by BASF Japan Ltd.). A specific example of the hindered phenol compound is N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)) (trade name: Iruganox1098, manufactured by BASF Japan Ltd.). A specific example of the phosphorus compound is Tris(2,4-di-tert-butylphenyl)phosphite (trade name: Irugafos168, manufactured by BASF Japan Ltd.).

[0021] The content of the heat stabilizer in the expanded beads is preferably 0.1 to 5 mass%, more preferably 0.2 to 3 parts by mass, and further preferably 0.3 to 1 mass%. When two or more kinds of heat stabilizers are contained, the total amount is preferably within the above range. In particular, when a hindered amine compound is used as the heat stabilizer, the content of the hindered amine compound in the expanded beads is preferably 0.1 to 1 mass%. When a hindered phenol compound is used as the heat stabilizer, the content of the hindered phenol compound in the expanded beads is preferably 0.05 to 0.5 mass%. When a phosphorus compound is used as the heat stabilizer, the content of the phosphorus compound in the expanded beads is preferably 0.05 to 0.5 mass%. When the content of the heat stabilizer is within the above range, the obtained expanded bead molding can be given better weather resistance.

[0022] (Coloring agent) The expanded beads of the present invention preferably contain a colorant. As the colorant, inorganic or organic pigments or dyes can be used. The colorant is used to improve the appearance of the resulting molded article and to enhance the design.

[0023] Examples of inorganic pigments include titanium oxide, carbon black, titanium yellow, iron oxide, ultramarine blue, cobalt blue, calcined pigments, metallic pigments, mica, pearl pigments, zinc white, precipitated silica, and cadmium red, with carbon black being preferred. Examples of organic pigments include monoazo pigments, condensed azo pigments, anthraquinone pigments, isoindolinone pigments, perinone pigments, quinacridone pigments, perylene pigments, thioindigo pigments, dioxazine pigments, phthalocyanine pigments, nitroso pigments, and organic fluorescent pigments. Examples of the dye include anthraquinone dyes, perinone dyes, basic dyes, acid dyes, and mordant dyes. Among these colorants, it is preferable to use organic pigments or inorganic pigments from the viewpoint of weather resistance, and inorganic pigments are preferable from the viewpoint of heat resistance and weather resistance. Of these, the colorant is preferably carbon black, that is, the expanded beads of the present invention preferably contain carbon black.

[0024] The content of the color pigment in the expanded beads is preferably 0.5 to 10% by mass, more preferably 0.8 to 5% by mass, and further preferably 1 to 3% by mass. In particular, when carbon black is used as the coloring pigment, the content of carbon black in the expanded beads is preferably 0.5 to 10 mass%, more preferably 0.8 to 5 mass%, and even more preferably 1 to 3 mass%. When the content of the coloring pigment is within the above range, excellent design properties can be imparted to the obtained expanded bead molding.

[0025] (Other resins and additives) The expanded beads of the present invention may contain other thermoplastic resins in addition to the polyamide resin and the polyarylene sulfide resin, so long as the purpose and effect of the present invention are not impaired. Examples of the other thermoplastic resins include polyethylene resins, polypropylene resins, polystyrene resins, vinyl acetate resins, thermoplastic polyester resins, acrylic acid ester resins, methacrylic acid ester resins, modified polyphenylene ether resins, polycarbonate resins, polyacetal resins, polybutylene terephthalate resins, polysulfone resins, polyethersulfone resins, polyamideimide resins, polyetherimide resins, polyetheretherketone resins, etc. From the viewpoint of obtaining expanded beads excellent in heat resistance, abrasion resistance, and chemical resistance, the content of other thermoplastic resins in the expanded beads of the present invention is preferably 10% by mass or less, more preferably 5% by mass or less, and even more preferably 3% by mass or less. It is particularly preferable that the expanded beads of the present invention are composed only of a polyamide resin and a polyarylene sulfide resin.

[0026] In addition to the polyamide resin and the polyarylene sulfide resin, various additives such as commonly used antistatic agents, conductivity imparting agents, lubricants, ultraviolet absorbers, flame retardants, metal deactivators, crystal nucleating agents, and fillers can be appropriately blended into the expanded beads of the present invention as necessary. The amount of these various additives to be added varies depending on the purpose of use of the molded product, but is preferably 25 parts by mass or less per 100 parts by mass of the base resin. More preferably, it is 15 parts by mass or less, even more preferably 10 parts by mass or less, and even more preferably 5 parts by mass or less.

[0027] (Characteristics of foam particles) The apparent density of the expanded beads of the present invention is 10 kg / m 3 or more, preferably 30 kg / m 3 More preferably, it is 50 kg / m 3 The apparent density of the expanded beads of the present invention is 300 kg / m 3 less than 200 kg / m 3 More preferably, it is 100 kg / m or less. 3 The following is the result. When the apparent density of the expanded beads is within the above range, a molded article made of the expanded beads is unlikely to shrink during molding, and a good expanded bead molded article can be easily obtained. The apparent density of the expanded beads is measured by the following method. A measuring cylinder containing water at 23°C was prepared and left for two days under the conditions of 50% relative humidity, 23°C, and 1 atm. 3 The mass W1 of the expanded beads is measured. Next, the expanded beads are submerged in the measuring cylinder using a wire net. Taking into account the volume of the wire net, the volume V1 [cm3] of the expanded beads is read from the rise in the water level. 3 ] is measured, and the mass W1 [g] of the foamed particles is divided by the volume V1 (W1 / V1), and the unit is [kg / m 3 The apparent density of the expanded beads is calculated by converting this to

[0028] The average cell diameter of the expanded beads of the present invention is preferably 20 μm or more, more preferably 30 μm or more, and even more preferably 40 μm or more. The average cell diameter of the expanded beads of the present invention is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less. When the average cell diameter of the expanded beads is within the above range, the surface properties of a molded article obtained by using the expanded beads are good. The average cell diameter of the expanded polyamide resin beads is measured by the following method. First, the expanded bead is divided into two parts passing through the center of the expanded bead, and the cut surface is photographed using a scanning electron microscope. Next, in the obtained cross-sectional photograph, straight lines are drawn at equal intervals in eight directions from near the center of the cut surface of the expanded bead, and the number of bubbles that intersect with the lines is counted. The total length of the straight lines is divided by the number of bubbles counted, and the resulting value is the bubble diameter of the expanded beads. This operation is performed in the same manner for 10 or more expanded beads, and the arithmetic average value of the bubble diameters of each expanded bead is the average bubble diameter of the expanded beads.

[0029] The closed cell ratio of the expanded beads of the present invention is 85% or more, preferably 88% or more, and more preferably 90% or more. When the closed cell ratio of the expanded beads satisfies the above range, expanded beads having a low apparent density are easily obtained. In addition, when an expanded bead molding is performed in a mold using expanded beads having a closed cell ratio that satisfies the above range, a molding having excellent fusion and recovery properties is easily obtained. The closed cell ratio is the ratio of the volume of the closed cells to the volume of all the cells in the expanded beads, and can be determined using an air comparison type specific gravity meter based on ASTM-D2856-70.

[0030] The melting point (Tm1) of the polyamide resin and the melting point (Tm2) of the polyarylene sulfide resin can be determined from the second DSC curve obtained under the following condition 1.

[0031] Condition 1 Based on the heat flux differential scanning calorimetry method of JIS K7121-1987, the expanded beads are used as a test piece, and the DSC curve measured when the test piece is heated and melted from 30°C to a temperature 30°C higher than the end of the melting peak at a heating rate of 10°C / min is taken as the first DSC curve. The test piece is then held at that temperature for 10 minutes, cooled to 30°C at a cooling rate of 10°C / min, and again heated and melted at a heating rate of 10°C / min to a temperature 30°C higher than the end of the melting peak is taken as the second DSC curve.

[0032] The second DSC curve shows a melting peak (I) specific to the polyamide resin and a melting peak (III) specific to the polyarylene sulfide resin at a higher temperature than the melting peak (I). The temperature at the apex of the melting peak (I) in the second DSC curve corresponds to the melting point (Tm1) of the polyamide resin, which is the raw material for producing the expanded beads, and the temperature at the apex of the melting peak (III) in the second DSC curve corresponds to the melting point (Tm2) of the polyarylene sulfide resin, which is the raw material for producing the expanded beads. The melting peak (I) and the melting peak (III) appear in both the first and second DSC curves. The temperatures at the apex of the melting peak (I) and the melting peak (III) may differ slightly between the first and second DSC curves, but the difference is 5°C or less, usually 2°C or less.

[0033] In the expanded beads of the present invention, in the second DSC curve, the difference [Tm2-Tm1] between the melting point (Tm1) of the polyamide resin and the melting point (Tm2) of the polyarylene sulfide resin is preferably 70° C. or more, more preferably 75° C. or more, and even more preferably 80° C. or more, and is preferably 130° C. or less, more preferably 110° C. or less, and even more preferably 100° C. or less. If the difference between the melting point of the polyamide resin and the melting point of the polyarylene sulfide resin is within the above range, molding shrinkage after molding can be effectively suppressed.

[0034] The melting point (Tm1) of the polyamide resin is preferably 180° C. or higher, more preferably 185° C. or higher. The melting point (Tm1) of the polyamide resin is preferably 250° C. or lower, more preferably 200° C. or lower. The melting point (Tm2) of the polyarylene sulfide resin is preferably 260° C. or higher, more preferably 270° C. or higher. The melting point (Tm2) of the polyarylene sulfide resin is preferably 300° C. or lower, more preferably 290° C. or lower.

[0035] In the first DSC curve, the temperature at the apex of the melting peak (I) specific to the polyamide resin is preferably 180° C. or higher, more preferably 185° C. or higher. The temperature at the apex of the melting peak (I) specific to the polyamide resin is preferably 250° C. or lower, more preferably 200° C. or lower. In the first DSC curve, the temperature at the apex of the melting peak (III) specific to the polyarylene sulfide resin is preferably 260° C. or higher, more preferably 270° C. or higher. The temperature at the apex of the melting peak (III) specific to the polyarylene sulfide resin is preferably 300° C. or lower, more preferably 290° C. or lower.

[0036] In the above condition 1, the first DSC curve using the expanded beads as the test piece may have a melting peak (II) at a higher temperature than the melting peak (I) specific to the polyamide resin, which is due to secondary crystallization of the polyamide resin formed by the thermal history until the resin particles are expanded to obtain the expanded beads. In this specification, the melting peak (II) is referred to as a high-temperature peak. There may be two or more high-temperature peaks (melting peaks (II)). In addition, the high-temperature peak (melting peak (II)) is not observed in the second DSC curve. The apex temperature of the high-temperature peak (melting peak (II)) appears at a higher temperature than the melting peak (I) in the first DSC curve using the expanded beads as the test piece. In addition, depending on the difference between the apex temperature of the melting peak specific to the polyamide resin and the apex temperature of the melting peak specific to the polyarylene sulfide resin, it is preferable that the apex temperature of the high-temperature peak (melting peak (II)) exists between the melting peak (I) and the melting peak (III) in the first DSC curve. That is, the first DSC curve obtained under the condition 1 preferably has melting peak (I), melting peak (II), and melting peak (III) in this order from the low temperature side. The high temperature peak appears at a higher temperature than the melting peak (I) inherent to the polyamide resin. Therefore, it is considered that the crystals of the high temperature peak are less likely to melt during molding in the mold than the melting peak (I) inherent to the polyamide resin, and are more likely to remain. In addition to containing the polyarylene sulfide resin, when the polyamide resin has a high temperature peak, it is considered that the molding shrinkage rate of the expanded bead molding can be further reduced.

[0037] The difference between the temperature at the apex of the melting peak (I) and the temperature at the apex of the high-temperature peak is preferably 10° C. or more, more preferably 12° C. or more, and even more preferably 15° C. or more. On the other hand, the difference between the temperature at the apex of the melting peak (I) and the temperature at the apex of the high-temperature peak is preferably 40° C. or less, more preferably 30° C. or less, and even more preferably 25° C. or less. In comparing the difference in temperature between the apex of the melting peak (I) and the high-temperature peak, if two or more high-temperature peaks appear in the first DSC curve, the temperature at the apex of the lowest-temperature high-temperature peak is compared with the temperature at the apex of the melting peak (I).

[0038] In the first DSC curve, the heat of fusion of the polyamide resin's inherent melting peak (I) is preferably 25 J / g or more, more preferably 30 J / g or more. The heat of fusion of the polyamide resin's inherent melting peak (I) is preferably 60 J / g or less, more preferably 50 J / g or less. In the first DSC curve, the heat of fusion of the polyarylene sulfide resin's inherent melting peak (III) is preferably 3 J / g or more, more preferably 5 J / g or more. The heat of fusion of the polyarylene sulfide resin's inherent melting peak (III) is preferably 15 J / g or less, more preferably 10 J / g or less. In the first DSC curve, the heat of fusion of the high-temperature peak (melting peak (II)) is preferably 1 J / g or more, more preferably 2 J / g or more. The heat of fusion of the high-temperature peak (melting peak (II)) is preferably 13 J / g or less, more preferably 10 J / g or less. Here, the temperature at the apex of each melting peak and the heat of fusion can be determined as follows.

[0039] The temperature of the apex of each melting peak can be obtained from the melting peak obtained in the first DSC curve obtained by heating from 30°C to a temperature 30°C higher than the end of the melting peak at a heating rate of 10°C / min by heat flux differential scanning calorimetry, which is condition 1. The heat of fusion of each melting peak can be obtained based on the DSC curve obtained under the following condition 2. As a measuring device, a high-sensitivity differential scanning calorimeter "EXSTAR DSC7020" (manufactured by SII NanoTechnology Co., Ltd.) can be used.

[0040] Condition 2 Based on the heat flux differential scanning calorimetry method of JIS K7122-1987, the expanded beads are used as test pieces, and are heated and melted at a heating rate of 10°C / min from 30°C to a temperature 30°C higher than the end of the melting peak to obtain a first DSC curve.

[0041] A specific explanation will be given below using Figure 1 (first DSC curve) as an example. For example, in the first DSC curve shown in Figure 1, there are three melting peaks, the lowest temperature peak is the melting peak (I) specific to polyamide resins, the second peak is the high temperature peak (melting peak (II)), and the highest temperature peak is the melting peak (III) specific to polyarylene sulfide resins. The temperature at the apex of each melting peak is the temperature at the point where the heat absorption of the respective peak is the largest.

[0042] The heat of fusion at the apex of each melting peak corresponds to the area of ​​each melting peak in the DSC curve shown in FIG. 1, and can be obtained as follows. A straight line is drawn between the point of 120° C. on the DSC curve and the point on the DSC curve indicating the melting end temperature of the melting peak (II) (baseline of the melting peak derived from the polyamide resin). The melting peaks (I) and (II) are divided by a straight line perpendicular to the temperature on the horizontal axis of the graph from the point on the DSC curve corresponding to the valley between the melting peaks (I) and (II) to the baseline of the melting peak derived from the polyamide resin. The area of ​​the divided low-temperature peak corresponds to the heat of fusion of the melting peak (I) inherent to the polyamide resin, and the area of ​​the divided high-temperature peak corresponds to the heat of fusion of the high-temperature peak (melting peak (II)) due to the secondary crystallization of the polyamide resin formed by the thermal history until the resin particles are expanded to obtain the expanded particles.

[0043] A straight line is drawn connecting the point at 240° C. on the DSC curve and the point indicating the melting end temperature of the melting peak (III) specific to the polyarylene sulfide resin (the baseline of the melting peak specific to the polyarylene sulfide resin). The area enclosed by the baseline of the melting peak derived from the polyamide resin and the DSC curve corresponds to the heat of fusion of the melting peak (III) inherent to the polyarylene sulfide resin.

[0044] <Method of manufacturing expanded beads> In the method for producing expanded polyamide resin beads of the present invention, expanded polyamide resin beads are produced by expanding resin particles having a mixed resin of the polyamide resin and the polyarylene sulfide resin as a base resin.

[0045] (Resin particles using mixed resin as base resin and manufacturing method thereof) The mass of each of the resin particles is appropriately set depending on the size and apparent density of the desired expanded particles, and is preferably 0.5 to 15.0 mg. If it is within the above range, the apparent density can be increased. From this viewpoint, the lower limit of the mass of the resin particles is more preferably 1.0 mg, and even more preferably 1.5 mg. On the other hand, the upper limit is more preferably 10.0 mg, and even more preferably 7.0 mg, and particularly preferably 5.0 mg.

[0046] From the viewpoint of obtaining expanded beads having excellent heat resistance, the melting point (Tm) of the resin particles constituting the expanded beads of the present invention is preferably 185° C. or higher, more preferably 188° C. or higher, and even more preferably 190° C. or higher. On the other hand, from the viewpoint of easy temperature control during expansion, the melting point (Tm) of the resin particles is preferably 250° C. or lower, more preferably 230° C. or lower, and even more preferably 225° C. or lower. The melting point of the resin particles refers to the melting point of a kneaded product obtained by previously kneading a polyamide resin and a polyarylene sulfide resin in an extruder or the like.

[0047] The melting point (Tm) of the resin particles constituting the expanded beads of the present invention is a value determined as the peak apex temperature of the melting peak of a DSC curve obtained by heat flux differential scanning calorimetry at a heating rate of 10°C / min, using the following procedure based on JIS K7121-1987: "measure the melting temperature after performing a certain heat treatment" (the heating rate and cooling rate in the conditioning of the test piece are both 10°C / min). When the DSC curve has multiple melting peaks, the peak apex temperature of the melting peak with the largest area is adopted as the melting temperature. Note that the test pieces of the resin particles are used after being stored in a desiccator under a nitrogen atmosphere and then vacuumed to prevent hydrolysis, for example, by avoiding high temperature and high humidity conditions.

[0048] The method for producing resin particles is not particularly limited, and can be obtained by known methods.For example, polyamide resin, polyarylene sulfide resin, and additives such as bubble adjuster as necessary are put into an extruder, kneaded to form a melt kneaded product, extrude the melt kneaded product in a strand shape from the small hole of the die attached to the tip of the extruder, and cut the extruded melt to a predetermined mass with a pelletizer, the hot cut method cuts the melt kneaded product immediately after extruding it into a gas phase, and the underwater cut method (UWC method) cuts the melt kneaded product immediately after extruding it into water, etc., can obtain resin particles.

[0049] (Example of manufacturing method of expanded beads) The method for producing expanded beads of the present invention includes an "impregnation step" of impregnating resin particles having the mixed resin as a base resin with a blowing agent, and an "expansion step" of expanding the resin particles having the mixed resin as a base resin impregnated with the blowing agent by heating, pressure change, volume change, or the like.

[0050] (foaming agent) In the method for producing expanded beads of the present invention, a physical foaming agent is preferably used as the foaming agent. Examples of the physical foaming agent include organic physical foaming agents such as aliphatic hydrocarbons such as propane, butane, pentane, hexane, and heptane, alicyclic hydrocarbons such as cyclopentane and cyclohexane, halogenated hydrocarbons such as chlorofluoromethane, trifluoromethane, 1,1-difluoroethane, 1,1,1,2-tetrafluoroethane, methyl chloride, ethyl chloride, and methylene chloride, and dialkyl ethers such as dimethyl ether, diethyl ether, and methyl ethyl ether. Examples of the inorganic physical foaming agent include carbon dioxide, nitrogen, helium, argon, and air. Among the physical blowing agents, from the viewpoints of having little impact on the environment, being non-flammable and having excellent safety, inorganic physical blowing agents are preferred, carbon dioxide or nitrogen are more preferred, and carbon dioxide is even more preferred.

[0051] (Example of manufacturing method) The method for producing the expanded beads of the present invention is not limited as long as it has the above-mentioned "impregnation step" and "expansion step". However, the following method is preferable: [1] a method in which resin particles are impregnated with a foaming agent, and then the resin particles impregnated with the foaming agent are removed without being expanded, and then heated in an expansion device to obtain expanded beads; and [2] a method in which resin particles dispersed in a dispersion medium in a sealed device are impregnated with a foaming agent, and the temperature is raised to near the softening temperature of the resin, and then the resin particles are released together with the dispersion medium outside the device under low pressure to obtain expanded beads, and the above method [2] is more preferable. The preferred production method, method [2], will be described below.

[0052] The method for producing the expanded beads of the present invention preferably comprises the following steps. (1) a dispersing step of dispersing the resin particles having the mixed resin as a base resin in water in a sealed container to obtain a dispersion; (2) an impregnation step of impregnating the resin particles in the dispersion with a physical foaming agent; (3) A holding step of holding the dispersion at a temperature 90° C. lower than the melting point (Tm) of the resin particles (Tm-90° C.) and lower than 50° C. lower than the melting point (Tm-50° C.) for a holding time of 1 minute to 60 minutes. (4) A foaming step in which the temperature (Te) of the dispersion immediately before foaming is set to a temperature (Tm-90°C) or higher and lower than a temperature (Tm-50°C) that is 90°C lower than the melting point (Tm) of the resin particles, and the resin particles containing a foaming agent are released from the sealed container together with water under a pressure lower than the pressure inside the sealed container to foam the resin particles. The method for producing the expanded beads of the present invention may include a step other than the above step, or other components may be added in the above step. The impregnation step and the holding step may be performed simultaneously, or the holding step may be performed prior to the impregnation step.

[0053] [Dispersion process] The dispersing step is a step of dispersing the resin particles in water in a closed container to obtain a dispersion liquid. The method for dispersing the resin particles in water is not particularly limited, and any known method can be used. For example, a dispersion can be obtained by adding the resin particles to water while stirring the water using a stirrer, and further stirring the water. In addition, it is preferable to add a dispersant such as an inorganic substance such as aluminum oxide, tricalcium phosphate, magnesium pyrophosphate, zinc oxide, kaolin, mica, talc, smectite, etc., or a dispersing aid such as an anionic surfactant such as sodium dodecylbenzenesulfonate, sodium alkanesulfonate, etc., to the dispersion liquid as needed. The mass ratio of the resin particles to the dispersing aid (resin particles / dispersing aid) is preferably 20 to 2000, more preferably 30 to 1000. In addition, the mass ratio of the dispersing agent to the dispersing aid (dispersing agent / dispersing aid) is preferably 1 to 500, more preferably 1 to 100.

[0054] [Impregnation process] The impregnation step is a step of impregnating the resin particles in the dispersion with a foaming agent. The resin particles can also be made to absorb water at the same time. The method of impregnating the resin particles with the foaming agent is not particularly limited, but it is preferable to disperse the resin particles in water in a pressurizable closed container such as an autoclave and impregnate the resin particles with the foaming agent. In addition to pressurization, it is preferable to heat the resin particles when impregnating them with the foaming agent, in order to sufficiently impregnate the resin particles with the foaming agent in a short time. In the case of pressurization, the impregnation step includes a step in which the pressure inside the sealed container rises from atmospheric pressure to the pressure during impregnation (hereinafter also referred to as the impregnation pressure). The step of impregnating the foaming agent includes a step of heating a dispersion liquid in which resin particles are dispersed in water from room temperature to a temperature during impregnation (hereinafter also referred to as the impregnation temperature).

[0055] The temperature during impregnation under heating is preferably 50°C or higher, more preferably 80°C or higher, from the viewpoint of sufficiently impregnating the resin particles with the foaming agent in a short period of time, and is preferably the melting point of the resin particles (Tm(°C)) or lower, more preferably (Tm-20(°C)) or lower.

[0056] In addition, from the viewpoint of sufficiently impregnating the resin particles with the foaming agent in a short time, the pressure during impregnation under pressure (hereinafter also referred to as the impregnation pressure) is adjusted so that the pressure inside the sealed container is preferably 1.5 MPa (G) or more, more preferably 2.5 MPa (G) or more, and is preferably 7 MPa (G) or less, and more preferably 5 MPa (G) or less, by adding the foaming agent to the container containing the dispersion. Note that "1.5MPa(G)" means that the gauge pressure is 1.5 MPa.

[0057] The dispersion step and the impregnation step also serve to make the resin particles absorb water. From the viewpoint of plasticizing the resin particles by sufficiently absorbing water, the total time of the step of obtaining a dispersion and the step of impregnating the foaming agent is preferably 20 minutes or more, more preferably 30 minutes or more. On the other hand, from the viewpoint of productivity of the expanded beads, the above time is preferably 60 minutes or less. The temperature rise rate in the impregnation step is preferably 10° C. / min or less, more preferably 7° C. / min or less, from the viewpoint of allowing the resin particles to sufficiently absorb water and plasticize them, whereas the temperature rise rate is preferably 1° C. / min or more, more preferably 2° C. / min or more, from the viewpoint of productivity of the expanded beads.

[0058] [Holding process] The holding step is a step of holding the dispersion at a temperature 90° C. lower than the melting point (Tm) of the resin particles (Tm-90° C.) and lower than 50° C. lower (Tm-50° C.) for a holding time of 1 minute to 60 minutes. The holding temperature of the dispersion in the holding step is, from the viewpoint of allowing the polyamide-based resin to sufficiently absorb water and plasticize it, and from the viewpoint of uniformly impregnating the mixed resin with the blowing agent, at least a temperature 90°C lower than the melting point (Tm) of the resin particles (Tm - 90°C), preferably at least a temperature 80°C lower (Tm - 80°C), more preferably at least a temperature 70°C lower (Tm - 70°C), even more preferably at least a temperature 65°C lower (Tm - 65°C), and is less than a temperature 50°C lower (Tm - 50°C), preferably at most a temperature 55°C lower (Tm - 55°C), more preferably at most a temperature 57°C lower (Tm - 57°C), even more preferably at most a temperature 59°C lower (Tm - 59°C).

[0059] Usually, when expanding beads are produced using a general-purpose resin such as a polypropylene resin as a base resin, the beads are kept at a temperature near the melting point of the raw material resin. However, in the method for producing expanded beads of the present invention, the beads are produced by keeping the temperature at a temperature 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C) or higher and 50°C lower than the melting point (Tm) of the resin particles (Tm-50°C). This is thought to be because polyamide resins are hygroscopic, so that the resin particles are plasticized by the water used as a dispersion liquid, and the melting point is significantly lowered, and as a result, it is possible to produce expanded beads having the desired apparent density and closed cell ratio at a temperature significantly lower than the melting point of the resin particles.

[0060] The holding time in the holding step is 1 minute or more, preferably 5 minutes or more, more preferably 10 minutes or more, and even more preferably 13 minutes or more, from the viewpoint of uniformly impregnating the mixed resin with the blowing agent and obtaining expanded beads having a high closed cell ratio. From the viewpoint of productivity of the expanded beads and prevention of hydrolysis of the polyamide resin, the holding time in the holding step is 60 minutes or less, preferably 40 minutes or less, more preferably 30 minutes or less, even more preferably 20 minutes or less, and even more preferably 18 minutes or less. By holding for the above time, it is possible to obtain expanded polyamide resin beads having a low apparent density and a high closed cell ratio. The holding step can be set in multiple stages within the above temperature range, and it is also possible to slowly increase the temperature within the temperature range over a sufficient period of time. From the viewpoint of easy production, it is preferable to set the temperature in one stage (the holding temperature is constant) within the above temperature range and hold for the above time.

[0061] The holding step is preferably carried out under pressure from the viewpoint of uniformly impregnating the mixed resin with the foaming agent, and is preferably maintained at the same pressure as the impregnation pressure. The pressure in the container containing the dispersion is preferably 1.5 MPa (G) or more, more preferably 2.5 MPa (G) or more. The pressure in the container containing the dispersion is preferably 7 MPa (G) or less, more preferably 5 MPa (G) or less.

[0062] [Foaming process] The foaming step is a step in which the resin particles impregnated with a foaming agent are foamed. The method for expanding the resin particles is not particularly limited, but a foaming method in which, following the holding step, the resin particles impregnated with a foaming agent are released together with water into an atmosphere under a pressure lower than that in the holding step (usually atmospheric pressure) to cause expansion is preferred.

[0063] The temperature Te of the dispersion immediately before foaming (hereinafter also referred to as the foaming temperature) is at least 90°C lower than the melting point (Tm) of the resin particles (Tm-90°C), preferably at least 80°C lower than the melting point (Tm-80°C), more preferably at least 70°C lower than the melting point (Tm-70°C), and even more preferably at least 65°C lower than the melting point (Tm-65°C), from the viewpoint of obtaining foamed particles having a low apparent density and a high closed cell ratio. The foaming temperature is less than 50°C lower than the melting point (Tm) of the resin particles (Tm-50°C), preferably at most 55°C lower than the melting point (Tm) of the resin particles (Tm-55°C), more preferably at most 57°C lower than the melting point (Tm-57°C), and even more preferably at most 59°C lower than the melting point (Tm-59°C).

[0064] The pressure immediately before release in the foaming step (foaming pressure) is preferably 0.5 MPa (G) or more, more preferably 1.5 MPa (G) or more, and even more preferably 2.5 MPa (G) or more. The foaming pressure is preferably 10 MPa (G) or less, more preferably 7 MPa (G) or less, and even more preferably 5 MPa (G) or less.

[0065] [Foamed bead molding] The expanded bead molding of the present invention is an expanded bead molding in which the expanded beads are fused to each other. That is, the expanded bead molding of the present invention is an expanded bead molding obtained by molding the expanded beads of the present invention in a mold. The expanded beads of the present invention have excellent fusion and recovery properties and can suppress shrinkage after molding, so that the expanded bead molding can suppress shrinkage after molding and has a good appearance. The expanded bead molding obtained by molding the expanded beads of the present invention in a mold can suppress shrinkage after molding, so that a thick molding can be suitably obtained. The thickness of the expanded bead molding is preferably 30 mm or more, and more preferably 40 mm or more. The in-mold molding method can be a conventionally known method, but it is preferable to use heating with steam. The polyamide resin in the expanded beads absorbs water and plasticizes by steam, making it possible to reduce the molding pressure. If the obtained molded body is dried to remove the moisture, it will return to the original physical properties of the polyamide resin, and the molded body will have high heat resistance.

[0066] The expanded beads of the present invention can be used to produce an expanded bead molding having excellent moldability in a mold. Specifically, the expanded beads have excellent secondary foaming properties when molding in a mold to obtain a molded product. In addition, the water cooling time can be shortened, which is preferable because the entire molding time can be shortened. The water-cooling time of the expanded bead molding is obtained as follows. First, the obtained expanded beads are filled into a mold, and in-mold molding is performed by steam heating to obtain a plate-shaped expanded bead molding. The heating method is as follows: with the drain valves of both molds open, steam is supplied for 5 seconds to perform preheating (exhaust process), and then steam is supplied from the moving mold, and then steam is supplied from the fixed mold, and the molding is heated to the molding heating steam pressure (molding pressure = molding steam pressure). After heating, the pressure is released, and the molding is water-cooled until the surface pressure due to the foaming force of the molding falls to 0.02 MPa (gauge pressure), and then the mold is opened and the molding is removed from the mold. The water-cooling time of the expanded bead molding is the water-cooling time (seconds) required from the start of water-cooling until the surface pressure reaches 0.02 MPa (gauge pressure).

[0067] The bulk density of the expanded bead molding obtained by using the expanded beads of the present invention is preferably 10 kg / m 3 More preferably, it is 20 kg / m 3 More preferably, it is 40 kg / m 3 The bulk density of the expanded bead molding obtained by using the expanded beads of the present invention is preferably 250 kg / m 3 More preferably, it is 200 kg / m or less. 3 More preferably, it is 100 kg / m or less. 3 The bulk density of the expanded bead molding is measured by the following method. The mass of the molded body is divided by the external dimensions and expressed in units of [kg / m 3 The bulk density of the molded body can be calculated by converting the bulk density into the mass per unit area (mass mass). EXAMPLES

[0068] The present invention will be described in detail below with reference to examples, but the present invention is not limited thereto.

[0069] Various physical properties of the resin particles, expanded particles and molded articles in each example were measured by the following methods.

[0070] [Measurement method] [Melting Point] The melting points of polyamide resins, polyarylene sulfide resins, and resin particles were measured by heat flux differential scanning calorimetry based on JIS K7121-1987. Under the condition of a nitrogen inflow rate of 30 mL / min, the resin was heated and melted from 30°C to a temperature 30°C higher than the end of the melting peak at a heating rate of 10°C / min (first heating), then held at that temperature for 10 minutes, cooled to 30°C at a cooling rate of 10°C / min, and heated and melted again at a heating rate of 10°C / min to a temperature 30°C higher than the end of the melting peak. The melting points were determined as the peak apex temperature of the melting peak of the second DSC curve. Note that a high-sensitivity differential scanning calorimeter "EXSTAR DSC7020" (manufactured by SII Nano Technology Co., Ltd.) was used as the measuring device. The resin particles and expanded particles used as test pieces were placed in a desiccator in a nitrogen atmosphere to avoid high temperature and high humidity conditions and to prevent hydrolysis, and then vacuum-sucked and stored for 24 hours with a moisture content of 1,000 ppm by mass or less before being used in the measurement of melting point.

[0071] 〔density〕 It was determined based on the method described in ISO 1183-3.

[0072] [Flexural modulus (MPa)] The flexural modulus of polyamide resin was determined by measurement in accordance with JIS K7171: 2016. The flexural modulus was measured by preparing a resin test piece having a thickness of 4 mm, a width of 10 mm, and a length of 80 mm, and leaving the test piece at rest for 72 hours at room temperature of 23°C and humidity of 50%, and then measuring it with an autograph AGS-10kNG (manufactured by Shimadzu Corporation) testing machine under the conditions of a support distance of 64 mm, an indenter radius R of 15.0 mm, a support table radius R of 25.0 mm, a test speed of 2 mm / min, a room temperature of 23°C, and a humidity of 50%, and the average of the calculated values ​​(5 points) was used.

[0073] [Peak apex temperature and heat of fusion] The expanded particles were used as test pieces, and the temperature was raised from 30°C to a temperature 30°C higher than the end of the melting peak at a heating rate of 10°C / min by heat flux differential scanning calorimetry. The first DSC curve was obtained by heating the specimens at a rate of 10°C / min, and the temperature and heat of fusion of each melting peak were calculated from the melting peaks. The measurement device used was a high-sensitivity differential scanning calorimeter "EXSTAR DSC7020" (manufactured by SII NanoTechnology). The following explains the first DSC curve with reference to Figure 1. In the first DSC curve shown in FIG. 1, there are three melting peaks; the lowest temperature peak is the melting peak (I) specific to the polyamide resin, the second peak is the high temperature peak (melting peak (II)), and the highest temperature peak is the melting peak (III) specific to the polyarylene sulfide resin. The temperature of the apex of each melting peak is the temperature of the most endothermic point of the respective peak. The heat of fusion at the apex of each melting peak corresponds to the area of ​​each melting peak in the DSC curve shown in FIG. 1, and was determined as follows.

[0074] First, a straight line was drawn connecting the point at 120° C. on the DSC curve and the point indicating the melting end temperature of the melting peak (II) on the DSC curve (the baseline of the melting peak derived from the polyamide resin). The melting peak (I) and the melting peak (II) were divided by a straight line perpendicular to the temperature on the horizontal axis of the graph from a point on the DSC curve corresponding to the valley between the melting peak (I) and the melting peak (II) to the baseline of the melting peak derived from the polyamide-based resin. The area of ​​the divided peak on the low temperature side corresponds to the heat of fusion of the melting peak (I) specific to the polyamide resin, and the area of ​​the divided peak on the high temperature side corresponds to the heat of fusion of the high-temperature peak (melting peak (II)) derived from the polyamide resin. Next, a straight line was drawn connecting the point at 240° C. on the DSC curve and the point indicating the melting end temperature of the melting peak (III) specific to the polyarylene sulfide resin (baseline of the melting peak specific to the polyarylene sulfide resin). The area enclosed by the baseline of the melting peak derived from the polyamide resin and the DSC curve corresponds to the heat of fusion of the melting peak (III) inherent to the polyarylene sulfide resin.

[0075] [Apparent density of expanded beads] A measuring cylinder containing water at 23°C was prepared and left for two days under the conditions of 50% relative humidity, 23°C, and 1 atm. 3 The mass W1 of the expanded beads was measured. Next, the expanded beads were submerged in the measuring cylinder using a wire net. Taking into account the volume of the wire net, the volume V1 [cm3] of the expanded beads was read from the rise in the water level. 3 ] is measured, and the mass W1 [g] of the foamed particles is divided by the volume V1 (W1 / V1), and the unit is [kg / m 3 The apparent density of the expanded beads was calculated by converting the density into the mass ratio (μm).

[0076] [Average bubble diameter of expanded beads] First, the expanded beads were divided into approximately two parts along the center of the expanded beads, and the cut surface was photographed with a scanning electron microscope. Next, in the obtained cross-sectional photograph, straight lines were drawn at equal intervals in eight directions from the center of the cut surface of the expanded beads, and the number of bubbles intersecting with the straight lines was counted. The total length of the straight lines was divided by the number of bubbles counted to obtain the bubble diameter of the expanded beads. This operation was carried out in the same manner for 10 expanded beads, and the arithmetic average value of the bubble diameters of each expanded bead was taken as the average bubble diameter of the expanded beads.

[0077] [Closed cell ratio of expanded beads] The true volume Vx of the foamed beads (the sum of the volume of the resin that constitutes the foamed beads and the total volume of the air bubbles in the closed cell part inside the foamed beads) was measured according to procedure C described in ASTM-D2856-70. To measure this true volume Vx, an air comparison specific gravity meter "930" manufactured by Toshiba Beckman Co., Ltd. was used. Next, the closed cell ratio was calculated according to the following formula (1), and the arithmetic average of the five measurement results was calculated. Closed cell ratio (%)=(Vx-W / ρ)×100 / (Va-W / ρ) (1) Vx: The true volume of the foam particles measured by the above method (cm 3 ) Va: Apparent volume of foam particles (cm 3 ) W: Mass of the sample for measuring foam particles (g) ρ: Density of the resin that composes the foamed particles (g / cm 3 )

[0078] [Bulk density of molded body] The expanded beads obtained in each of the Examples and Comparative Examples were used to prepare expanded bead molded articles by the method described in Example 1 [Production of expanded mixed resin bead molded article]. The mass of the obtained molded body was divided by the external dimensions and expressed in units of [kg / m 3 The bulk density of the molded body was calculated by converting the bulk density into the mass per unit area (mass sieve).

[0079] [Evaluation method] [Molding shrinkage rate of molded body] Using the expanded beads obtained in each Example and Comparative Example, an expanded bead molding was produced by the method described in [Production of Expanded Mixed Resin Bead Molding] in Example 1. After leaving it to stand for 24 hours in an environment of 23°C and 50% relative humidity, the dimensions of the expanded bead molding were measured, and the value shown by the following formula when the length, width, and thickness were respectively a', b', and c' and the dimensions (internal dimensions) of the mold, which are the length, width, and thickness, were respectively a, b, and c, was taken as the molding shrinkage rate (%) of the molding. The smaller the value of the molding shrinkage rate of the molding, the more suppressed the molding shrinkage rate is, and this is preferable. (formula) Mold shrinkage rate (%) = [(a-a') / a + (b-b') / b + (c-c') / c] x 100 / 3

[0080] [Weldability] The fusion rate of the resulting expanded bead moldings was measured to evaluate their fusion properties. A fusion rate of 90% or more was rated "A," and a fusion rate of less than 90% was rated "C." The fusion rate of the expanded bead molding was measured by the following method. On one side of the surface of the expanded bead molding obtained in each Example and Comparative Example, a cutter knife was used to make a cut in the thickness direction at a position that divided the vertical length of the test piece into two equal parts, with a depth of about 10 mm, and the molding was folded and broken from the cut. The ratio (m / n×100[%]) of the number of expanded beads present on the fracture surface that had undergone material destruction to the number n of all expanded beads present on the fracture surface was calculated. When the molding could not be broken even by folding, the fusion rate was taken as 100%. The above measurement was carried out five times using different test pieces, and the material destruction rate for each was calculated, and the arithmetic average of the material destruction rates was taken as the fusion rate.

[0081] [Recovery] The expanded bead moldings obtained in each Example and Comparative Example were allowed to stand for 24 hours in an environment of 23°C and 50% relative humidity, after which the thicknesses of the center and the four corners of the expanded bead moldings obtained were measured. If the ratio of the thickness of the center to the thickest part among the four corners was 90% or more, it was evaluated as "A", and if it was less than 90%, it was evaluated as "C".

[0082] 〔exterior〕 The surface of the expanded bead molding obtained in each Example and Comparative Example was visually inspected, and the appearance was evaluated according to the following criteria. (Evaluation Criteria) A: Beautiful surface and excellent appearance B: Voids (gaps between foam particles) were found on the surface of the molded product, and the appearance was slightly poor. C: Voids (gaps between foam particles) were clearly observed on the surface of the molded product, and the appearance was poor.

[0083] Example 1 [Production of mixed resin particles] The extruder was fed with polyamide resin "6434B" (manufactured by Ube Industries, Ltd.), linear polyarylene sulfide resin "FZ-2100" (manufactured by DIC Corporation) in the blending ratio shown in Table 1, talc "Talc Powder PK-S" (manufactured by Hayashi Kasei Co., Ltd.) was fed as a cell regulator to 0.3 mass%, and aromatic polycarbodiimide "Stabaxol P100" (manufactured by Rhein Chemie) was fed as an end-capping agent to 1 mass%, and melt-kneaded to obtain a melt-kneaded product. The melt-kneaded product was extruded as a strand with a circular cross section from the hole of the nozzle attached to the tip of the extruder, and the extruded strand was water-cooled, then cut with a pelletizer so that the average mass per piece was 2 mg, and dried to obtain pellet-shaped mixed resin particles. The melting point of the resin particles was 186°C. The polyamide resin "6434B" is a polyamide 6 / 66 / 12 copolymer (nylon 6 / 66 / 12), with a melting point (Tm) of 186°C and a density of 1.12g / cm 3 , flexural modulus: 1070 MPa, product name: UBE Nylon 6434B.

[0084] [Production of mixed resin foam particles] 500g of the obtained mixed resin particles and 3.5 liters of water as a dispersion medium were charged into a 5-liter autoclave equipped with a stirrer, and further, 0.3 parts by mass of kaolin as a dispersant and 0.004 parts by mass of sodium alkylbenzenesulfonate as a surfactant were added to 100 parts by mass of the mixed resin particles. While stirring the contents in the autoclave, the temperature was raised from room temperature (23°C) to the impregnation temperature (131°C), and carbon dioxide as a foaming agent was pressed into the autoclave until the pressure in the autoclave reached the impregnation pressure (4.0 MPa (G)). At this time, the temperature rise time from room temperature (23°C) to the impregnation temperature (131°C) was 40 minutes. Next, the temperature was held at 131°C and 4.0 MPa (G) for 15 minutes. The mixed resin particles impregnated with the foaming agent were then released together with the dispersion medium under atmospheric pressure (0.1 MPa). The foaming temperature (temperature of the dispersion liquid immediately before foaming) was 131° C. The resulting expanded mixed resin particles were cured in an oven at 60° C. for 24 hours, and then slowly cooled to obtain expanded mixed resin particles. The obtained expanded mixed resin beads were subjected to the above-mentioned evaluations, and the results are shown in Table 1.

[0085] [Production of mixed resin foamed bead moldings] Next, the expanded resin beads were used to produce an expanded bead molding. After the mold was clamped, the obtained foamed mixed resin beads were filled into a flat mold measuring 200 mm long x 65 mm wide x 40 mm thick, and molding was carried out in the mold by steam heating to obtain a plate-shaped foamed bead molding. The heating method was as follows: with the drain valves on both sides of the molds open, steam was supplied for 5 seconds to perform preheating (exhaust process), then with the drain valve on the fixed side open, steam was supplied from the moving side mold, and with the drain valve on the moving side open, steam was supplied from the fixed side mold, after which the exhaust valve was closed and heating was performed up to a molding heating steam pressure of 0.12 MPa (molding pressure = molding steam pressure). After heating, the pressure was released and the molded product was cooled with water until the surface pressure due to the foaming force of the molded product decreased to 0.02 MPa (gauge pressure), after which the mold was opened and the molded product was removed from the mold.The molded product was then placed in an oven at 80°C and removed after 24 hours to obtain a mixed resin foamed particle molded product. The obtained expanded molded article of mixed resin beads was evaluated as described above. The results are shown in Table 1.

[0086] Example 2 Mixed resin particles, expanded mixed resin particles, and a molded article made from expanded mixed resin particles were obtained in the same manner as in Example 1, except that the polyarylene sulfide resin "FZ-2100" (manufactured by DIC Corporation) was replaced with a linear polyarylene sulfide resin "MA-505" (manufactured by DIC Corporation) in the blending ratio shown in Table 1. The obtained expanded mixed resin particles and molded article made from expanded mixed resin particles were evaluated as described above. The results are shown in Table 1.

[0087] Example 3, Comparative Example 1 and Comparative Example 3 Mixed resin particles, expanded mixed resin particles, and expanded mixed resin particle moldings were obtained in the same manner as in Example 1, except that the blending ratio of polyarylene sulfide resin "FZ-2100" (manufactured by DIC Corporation) was adjusted to the amounts shown in Table 1. The obtained expanded mixed resin particles and expanded mixed resin particle moldings were evaluated as described above. The results are shown in Table 1. The crystallite size of the expanded bead molding obtained in Example 3 was measured and found to be 9 nm. The crystallite size of the expanded bead molding was determined by the following method. The X-ray diffraction (XRD) measurement of the obtained expanded bead molding was performed by a reflection method using an X-ray scattering device "Smart Lab SE" (manufactured by Rigaku Corporation). A one-dimensional semiconductor detector D / teX Ultra250 was used as the detector. The expanded bead molding was sliced ​​so that the sample thickness was about 2.0 to 3.0 mm. In addition, the standard substance lanthanum hexaboride was measured to determine b. The obtained one-dimensional X-ray diffraction profile was subjected to peak separation into a diffraction peak derived from crystals and a diffraction peak derived from amorphous crystals, assuming a Gaussian function as the peak shape. The full width at half maximum β (rad) of the peak having the narrowest peak width among the peaks obtained by peak separation was calculated, and the crystallite size D of the expanded bead molding was calculated according to the following formula (2) using the full width at half maximum β.

[0088]

number

[0089] Example 4 The mixed resin particles, the expanded mixed resin particles, and the expanded mixed resin particle moldings were obtained in the same manner as in Example 1, except that the carbon black "ROYAL BLACK 986P" (manufactured by Koshigaya Chemical Industry Co., Ltd.) was supplied in the amount shown in Table 1. The expanded mixed resin particles and the expanded mixed resin particle moldings obtained were evaluated as described above. The results are shown in Table 1.

[0090] Example 5 As a heat stabilizer, a hindered amine compound [Bis(2,2,6,6,-tetramethyl-4-piperidyl)sebacate, trade name: Tinuvin770, manufactured by BASF Japan Co., Ltd.] was supplied so as to be 0.18% by mass, a hindered phenol compound [N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)), trade name: Iruganox1098, manufactured by BASF Japan Co., Ltd.] was supplied so as to be 0.09% by mass, and a phosphorus compound [Tris(2,4-di-tert-butylphenyl)phosphite, trade name: Irugafos168, manufactured by BASF Japan Co., Ltd.] was supplied so as to be 0.09% by mass. The mixed resin particles, the expanded mixed resin particles, and the expanded mixed resin particle moldings were obtained in the same manner as in Example 3. The obtained expanded mixed resin particles and the expanded mixed resin particle moldings were evaluated as described above. The results are shown in Table 1.

[0091] Example 6 Carbon black "ROYAL BLACK 986P" (Koshigaya Chemical Industry Co., Ltd.) was supplied in the amount shown in Table 1, and as a heat stabilizer, a hindered amine compound [Bis(2,2,6,6,-tetramethyl-4-piperidyl)sebacate, trade name: Tinuvin770, BASF Japan Co., Ltd.] was supplied in an amount of 0.18 mass%, a hindered phenol compound [N,N'-hexane-1,6-diylbis(3-(3,5-di-tert-butyl-4-hydroxyphenylpropionamide)), trade name: Iruganox1098, BASF Japan Co., Ltd.] was supplied in an amount of 0.09 mass%, and a phosphorus compound [Tris(2,4-di-tert-butylphenyl)phosphite, trade name: Irugafos168, BASF Japan Co., Ltd.] was supplied in an amount of 0.09 mass%. Except for this, mixed resin particles, mixed resin expanded particles, and mixed resin expanded particle moldings were obtained in the same manner as in Example 1. The obtained expanded mixed resin beads and expanded molded articles of the expanded mixed resin beads were evaluated as described above. The results are shown in Table 1.

[0092] Comparative Example 2 Polyamide-based resin particles, expanded polyamide-based resin particles, and expanded polyamide-based resin particles molded articles were obtained in the same manner as in Example 1, except that the polyarylene sulfide-based resin "FZ-2100" (manufactured by DIC Corporation) was not used and only the polyamide-based resin "6434B" was supplied as the resin. The obtained expanded polyamide-based resin particles and expanded polyamide-based resin particles molded articles were evaluated as described above. The results are shown in Table 1.

[0093] [Table 1]

[0094] From the results shown in Table 1, the expanded bead moldings obtained in the examples were suppressed in shrinkage after molding and had good appearance. Thus, it is found that the expanded beads obtained in the examples have excellent fusibility and recovery properties, and it is possible to obtain expanded bead moldings that are suppressed in shrinkage after molding and have good appearance as described above. [Explanation of symbols]

[0095] 1. Melting peak specific to polyamide resin (I) 2 High-temperature peak (melting peak (II)) 3. Melting peak specific to polyarylene sulfide resins (III)

Claims

1. The expanded beads have a mixed resin of a polyamide resin and a polyarylene sulfide resin as a base resin, The apparent density of the expanded beads is 10 to 300 kg / m 3 and the difference [Tm2-Tm1] between the melting point (Tm1) of the polyamide resin and the melting point (Tm2) of the polyarylene sulfide resin is 70 to 130°C; The expanded beads have a blending ratio of the polyarylene sulfide resin to 100 parts by mass of the polyamide resin of from 5 to 40 parts by mass.

2. The expanded beads according to claim 1 , wherein the polyarylene sulfide resin is a polyphenylene sulfide resin.

3. 3. The expanded beads according to claim 1, wherein the average cell diameter of the expanded beads is 30 to 150 μm.

4. The expanded beads according to any one of claims 1 to 3, wherein the polyamide resin is a polyamide copolymer having a melting point of 185 to 250°C.

5. The expanded beads described in any one of claims 1 to 4, wherein the difference [Tm2-Tm1] between the melting point (Tm1) of the polyamide-based resin and the melting point (Tm2) of the polyarylene sulfide-based resin is 80 to 100°C.

6. The expanded beads according to any one of claims 1 to 5, comprising at least one heat stabilizer selected from the group consisting of hindered amine compounds, hindered phenol compounds, and phosphorus compounds.

7. The expanded beads according to any one of claims 1 to 6, wherein the expanded beads contain carbon black.

8. 8. An expanded bead molding in which the expanded beads according to any one of claims 1 to 7 are fused to each other.

Citation Information

Patent Citations

  • Production of polymer alloy

    JP1994298945A

  • Polyamide foams and their production

    JP1996283568A

  • Polyamide-based resin foam and its production

    JP2000103960A

  • Expanded polyamide

    JP2011526315A

  • Polyphenylene sulfide-based resin composition for foaming and foam molded article

    JP2012082299A